CO2-switchable polymer-hybrid silver nanoparticles and their gas-tunable catalytic activity. Issue 78 (26th October 2017) - Guo, Zanru; Gu, Hongjian; Ma, Wei; Chen, Qiang; He, Zhanfeng; Zhang, Jiali; Liu, Yongxin; Zheng, Longzhen; Feng, Yujun
Abstract : A new type CO2 -switchable AgNPs hybrids show switchable and monotonous tunable catalytic activity for the reduction of 4-nitrophenol by varying the flow rate of CO2 purged into the reaction system. Abstract : The design of controllable or "signal-triggered" metal nanoparticles is one of the emerging trends in nanotechnology and advanced materials. CO2 -switchable polymer-hybrid silver nanoparticles (AgNPs) were prepared by a one-pot reaction reducing AgNO3 and trithioester terminated PDEAEMA with sodium borohydride (NaBH4 ). The hybrids showed a long-term stability, and their size and size distribution can be easily modulated by tuning the molar ratio of polymers to AgNO3 . The hybrids not only exhibit hydrophobic–hydrophilic transitions in immiscible mixed solvents, but also undergo a switchable dispersion/aggregation states upon alternately treating with CO2 and N2 . Moreover, this smart hybrid was preliminarily used as catalyst for the reduction of 4-nitrophenol. The catalytic activity of the hybrids can be switched and monotonously tuned by varying the flow rate of CO2 purged into the reaction system, which may open a new avenue for tailoring the catalytic activity of metal nanoparticles toward a given reaction.